PENGARUH MODEL PEMBELAJARAN SFE (STUDENT FACILITATOR AND EXPLAINING) BERBASIS BBL (BRAIN-BASED LEARNING) TERHADAP HASIL BELAJAR DAN RETENSI SISWA - Ken Izmi Sasmi Afrik Rojanna; Jekti Prihatin; Kamalia Fikri (FKIP Universitas Jember, 2020)
Educational problems that exist in the classroom in general, namely the learning process is still dominated by teacher-centered learning and theoretical resulting in low retention and student learning outcomes. One way to improve student retention and learning outcomes requires a revolutionary paradigm by a teacher in the learning process. The BBL (Brain-Based Learning) based SFE (Student Facilitator and Explaining) learning model can improve student achievment and retention. The purpose of this study was to determine the effect of BBL (Brain-Based Learning) SFE (Student Facilitator and Explaining) learning models on student achievment and retention. This type of research was a quasi experimental. Based on the results of the analysis does not significantly influence the student cognitive (p = 0.134), influencing the student psychomotor (p = 0.006), significantly influence the student affective (p = 0,000), and significantly influence the student retention (p = 0,000).